2022
DOI: 10.3390/atmos13020236
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of the Standardized Precipitation Index (SPI) for the Evaluation of Drought in the Arroyo Pechelín Basin, Colombia, under Zero Monthly Precipitation Conditions

Abstract: The evaluation of the meteorological drought is fundamental for the management of the water resource. One of the most used indices to evaluate the drought is the standardized precipitation index (SPI) due to its practicality and evaluation in a variety of time scales, however, this uses precipitation as the only variable, depending on the deviations in the precipitation values. This is important when evaluating the SPI, because in some ecosystems close to the equatorial zone, there are very warm periods with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…CHIRPS data also measured the best metrics in relation to PERSIAN-CDR data for the Mearim river basin in the transition area of the Amazon and Caatinga in the state of Maranhão [65]. The authors also highlighted that in the rainiest period, between December and May, CHIRPS data performed better.…”
Section: Annual Scalementioning
confidence: 86%
See 1 more Smart Citation
“…CHIRPS data also measured the best metrics in relation to PERSIAN-CDR data for the Mearim river basin in the transition area of the Amazon and Caatinga in the state of Maranhão [65]. The authors also highlighted that in the rainiest period, between December and May, CHIRPS data performed better.…”
Section: Annual Scalementioning
confidence: 86%
“…Although it is widely used to identify drought events [65][66][67], the SPI is also used to characterize rainfall anomalies in Brazil [68] and to understand the variability of rainfall [8,[69][70][71].…”
Section: Standardized Precipitation Indexmentioning
confidence: 99%
“…Furthermore, the developed two-dimensional index system has been compared with the already existing, most widely used drought monitoring index SPI [14]. It's noteworthy that the SPI is built upon the analysis of precipitation data only [28]. The common approach of developing the SPI involves fitting a gamma distribution to the precipitation data [19].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing individual factors contributing to droughts falls short in offering a comprehensive understanding of the complex ramifications of drought events [11,35]. Consequently, relying solely on metrics like Standardized Precipitation Index (SPI) proves insufficient in gauging drought severity because it primarily assesses the influence of rainfall [14,28]. However, temperature is a crucial parameter in discerning droughts since certain temperature conditions can offset the effects of rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of the Standardized Precipitation Index (SPI) previously reported by the same research team while assessing the vegetation dynamics in the study area [9], SPEI is here used in order to overcome some limitations of the former. In fact, even when SPI remains widely [11][12][13], this index is thought to be an incomplete way to apprehend drought due to the fact that it relies only on precipitation but, drought as climatic phenomenon implies temperature and evapotranspiration considerations. Thus, many authors strongly suggested the use of multidimensional approaches to better characterize climatic events [14,15].…”
Section: Introductionmentioning
confidence: 99%